Automatic Tumor Classification of Brain MRI Images - Vani, V; Kalaiselvi Geetha, M (International Journal of Computer Sciences and Engineering, 2025)
Brain tumor classification is an active research area in medical image processing and pattern recognition. Brain tumor is an abnormal mass of tissue in which some cells grow and multiply uncontrollably, apparently unregulated by the mechanisms that control normal cells. The growth of a tumor takes up space within the skull and interferes with normal brain activity. The detection of the tumor is very important in earlier stages. Automating this process is a challenging task because of the high diversity in the appearance of tumor tissues among different patients and in many cases similarity with the normal tissues. This paper depicts a novel framework for brain tumor classification based on Gray Level Co-occurrence matrix (GLCM) statistical features are extracted from the brain MRI images, which signify the important texture features of tumor tissue. The experiments are carried out using BRATS dataset, considering two classes viz (normal and abnormal) and the extracted features are modeled by Support Vector Machines (SVM), k-Nearest Neighbor (k-NN) and Decision Tree(DT)for classifying tumor types. In the experimental results, Decision Tree exhibit effectiveness of the proposed method with an overall accuracy rate of 98.68%, this outperforms the SVM and k-NN classifiers.